A review of social inclusion guidelines, methods and tools - Cullen, Beth; Debevec, Liza (CGIAR GENDER Impact Platform, 2024)
The concept of social inclusion—the process of improving the terms of participation in society—is gaining influence. This paper identifies, reviews and curates social inclusion resources for agri-food systems research. The paper analyzes how resources frame social inclusion and assesses the extent they adhere to social inclusion principles. After an introduction to social inclusion and its evolution since the 1970s, we discuss how social inclusion has been mobilised within the agri-food systems research sector and the development landscape. Using a mostly qualitative approach, we classify and analyze a selection of social inclusion guidelines, frameworks, methods and tools. We evaluate this selection based on criteria identified from a review of social inclusion literature, highlight good practices and identify gaps. In conclusion, we offer recommendations to inform the design and use of future AR4D social inclusion resources.